The non-designer's design book : Design and typographic principles for the visual novice - Williams, Robin, ....- (San Francisco : Peachpit Press, 2015)
For nearly 20 years, designers and non-designers alike have been introduced to the fundamental principles of great design by author Robin Williams. Through her straightforward and light-hearted style, Robin has taught hundreds of thousands of people how to make their designs look professional using four surprisingly simple principles. Now in its fourth edition, The Non-Designer's Design Book offers even more practical design advice, including a new chapter on the fundamentals of typography, more quizzes and exercises to train your Designer Eye, updated projects for you to try, and new visual and typographic examples to inspire your creativity.